Percement des tubes dans les échangeurs de chaleur - . YOUNSI Toufik (My University, 2012)
Corrosion in industry is a phenomenon of current which are faced by maintenance crews and production of various units of the industrial pole of Arzew. This results in more or less prolonged stoppages of production lines, leaks sometimes dangerous to the health of staff, catastrophic bursting of pipes, contamination of the environment etc. For example the cutting of tubes in the reboiler is a thorny problem for the LNG complex. Problem prevention necessarily requires Knowledge of their cause, their mechanism and the effects they produce. Corrosion and scaling are among the main events to be monitored. Correct the parameters in time, is already the solution to a problem of maintenance
Keywords: Corrosion, Scaling, Environment, drilling pipes, reboilers.